PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PNS DI REKTORAT UNIVERSITAS TADULAKO PALU - Handayati, Oktarina (Katalogis, 2018)
The study is undertaken at the rectorate office of Tadulako University and aims to determine and analyze the influence of organizational culture (X1) and compensation (X2) on work satisfaction (Y). The study is expected to support the task accomplishment of civil servants at the rectorate of Tadulako University. This is a field study that is analyzed by multiple linear regression. The data used consists of primary and secondary data obtained through interviews and questionnaires distribution to 86 civil servants at the rectorate of Tadulako University. The result shows that organizational culture and compensation simultaneously and partially have positive influence on employees’ satisfaction.